Variation in posture quality across musical instruments and its impact during performances. Issue 2 (3rd April 2018) - Blanco-Piñeiro, Patricia; Díaz-Pereira, M. Pino; Martínez Vidal, Aurora
Abstract : Objective . Bad posture increases the risk that a musician may suffer from musculoskeletal disorders. This study compared posture quality required by different instruments or families of instruments. Methods . Using an ad-hoc postural observation instrument embracing 11 postural variables, four experts evaluated the postures of 100 students attending a Spanish higher conservatory of music. Results . The agreement of the experts' evaluations was statistically confirmed by a Cohen's κ value between 0.855 and 1.000 and a Kendall value between 0.709 and 1.000 ( p < 0.001 in all cases). Moreover, χ 2 tests revealed significant association between instrument families and seated posture with respect to pelvic attitude, dorsal curvature and head alignment in both sagittal and frontal planes. This analysis also showed an association between instrument families and standing posture with respect to the frontal plane of the axis of gravity, pelvic attitude, head alignment in the frontal plane, the sagittal plane of the shoulders and overall posture. Conclusions . While certain postural defects appear to be common to all families of instruments, others are more characteristic of some families than others. The instrument associated with the best posture quality was the bagpipe, followed by percussion and strings.